EFEKTIVITAS DAN EFISIENSI MESIN-MESIN DALAM SATU RANGKAIAN PADA PROSES PRODUKSI KAYU LAPIS (STUDI KASUS DI PT BASIRIH INDUSTRIAL) - Noor Fitriadi; Zainal Abidin; Budi Sutiya (Jurnal Sylva Scienteae, 2023)
The purpose of this study is to analyze the effectiveness and efficiency of the machines in the plywood production process at PT. Basirih Industrial. The method used includes the process of collecting data in the form of observations, interviews, and literature studies, as well as descriptive data analysis in the form of tables and calculation graphs which are then analyzed using the Effectiveness and Efficiency formula. The effectiveness value of using machines in one series at PT Basirih Industrial has reached a high effectiveness value of 100% on seven machines in the plywood production process including the Log cutting, Rotary, Continues Dryer, Glue Spreader, Hot press, Composser and Scraf joint stages and two the engine value is not high, namely at the Sizer and Sander stages it only reaches 91.66% and the engine efficiency value at PT Basirih Industrial ranges from 54.02% - 96.15%. The most efficient stage in the production process is the Hot Press stage of 96% and the lowest efficiency is the Composer, Sander and Rotary respectively 54.02%, 66.57% and 66.66%.Tujuan dari penelitian ialah menganalisis dari nilai efektifitas dan efisiensi mesin-mesin pada proses produksi di industri kayu lapis di PT. Basirih Industrial. Metode yang digunakan meliputi dari kumpulan data berupa data observasi, tahap wawancara, dan metode studi pustaka, serta analisis data secara deskriftif berupa tabel serta grafik hasil perhitungan yang selanjutya dianalisis menggunakan rumus Efektifitas dan Efesiensi. Nilai dari efektifitas penggunaan mesin pada satu rangkaian di PT Basirih Industrial sudah mencapai nilai efektifitas yang tinggi sebesar 100% pada tujuh mesin tahap proses produksi kayu lapis diantaranya tahap Log cutting, Rotary, Continues Dryer, Glue Spreader, Hot press, Composser dan Scraf joint dan dua mesin nilainya belunn tinggi yaitu pada tahap Sizer dan Sander hanya mencapai 91,66% dan Nilai efisiensi mesin pada PT Basirih Industrial berkisar antara 54,02% - 96,15%. Tahap yang paling efisien dalam proses produksi yaitu tahap Hot Press sebesar 96% dan efisiensi paling rendah yaitu pada Composer, Sander dan Rotary masing – masing 54,02%, 66,57% dan 66,66%.